Genetic variability and association study in some hulled and hulless genotypes of barley (Hordeum vulgare L.) in north western Himalayan region - Kumar, Amit; Kishore, Naval; Devlash, Rakesh; Singh, Gurudev (Journal of Cereal Research, 2018)
The experimental material comprising of 31 genotypes along with four checks of barley were evaluated in Randomized Block Design with three replications over two years during Rabi, 2016-17 and Rabi, 2017-18. Sufficient genetic variability was observed for all the characters in pooled over environments. High PCV and GCV (>20%) values along with high heritability coupled with high genetic advance were recorded for a number of grains per spike, biological yield per plant and seed yield per plant which indicated the predominance of additive gene action. Association study showed a significant and positive correlation of biological yield per plant, a number of grains per spike and number of tillers per plant with seed yield per plant. Path coefficient analysis also exhibited high positive direct and indirect contributions of these traits towards seed yield per plant indicating further selection based on these traits for effective improvement in barley. Â Doi.org/110.25174/2249-4065/2018/83717